2020
DOI: 10.3390/su12176788
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment for Building Energy Models Using Observed vs. Third-Party Weather Data Sets

Abstract: The use of building energy models (BEMs) is becoming increasingly widespread for assessing the suitability of energy strategies in building environments. The accuracy of the results depends not only on the fit of the energy model used, but also on the required external files, and the weather file is one of the most important. One of the sources for obtaining meteorological data for a certain period of time is through an on-site weather station; however, this is not always available due to the high costs and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Studies that have accounted for weather forecasts have usually incorporated only outdoor temperature [ 52 ], outdoor temperature and relative humidity [ 34 , 36 ] or temperature and solar irradiation [ 32 ] but not all influential weather parameters. Previous studies from the authors have shown that weather parameters such as wind speed can be very influential on the building’s load [ 70 ]. For this reason, this research introduced forecast data for outdoor temperature, relative humidity, direct normal irradiation, diffuse horizontal irradiation, wind speed and wind direction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have accounted for weather forecasts have usually incorporated only outdoor temperature [ 52 ], outdoor temperature and relative humidity [ 34 , 36 ] or temperature and solar irradiation [ 32 ] but not all influential weather parameters. Previous studies from the authors have shown that weather parameters such as wind speed can be very influential on the building’s load [ 70 ]. For this reason, this research introduced forecast data for outdoor temperature, relative humidity, direct normal irradiation, diffuse horizontal irradiation, wind speed and wind direction.…”
Section: Discussionmentioning
confidence: 99%
“…There are challenges in the calibration process for the measurement and verification of energy savings, which can be based on mathematical algorithms and physical-based models and are evaluated according to uncertainty analysis [5][6][7]. As stated by the ASHRAE Handbook: Fundamentals: SI edition (2017) [8], several difficulties prevent achieving a calibrated simulation [9][10][11][12]. One of them is the method used to measure the input parameters needed for the simulation, i.e., infiltration values [13][14][15][16].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Specific calibration techniques for building envelope calibration can be consulted in references (Ramos Ruiz et al 2016;Fernández Bandera and Ramos Ruiz 2017;Gutiérrez González et al 2020) and for heating ventilation and air conditioning systems (HVAC systems) in references (Pachano and Fernández Bandera 2021;Pachano et al 2022). The error for the weather has been evaluated in the following studies (Lucas Segarra et al 2020b;Gutiérrez González et al 2021) and for the weather forecast in references (Lucas Segarra et al 2019, 2020a.…”
Section: The Concept: Demand Side Managementmentioning
confidence: 99%